ÉCRIRE AVEC LES ANIMAUX : LES CHOIX INATTENDUS DE BARBEY D’AUREVILLY - TERMITE, Marinella (Studia Universitatis Babeș-Bolyai Philologia, 2019)
Writing with Animals: The Unexpected Choices of Barbey d’Aurevilly. In the pages of Jules Barbey d’Aurevilly, the presence of animals makes it possible to rethink the forms of scriptural cohabitation of humans and non-humans at a time when the appeal of science contributes to the development of a growing culture careful of a now problematic impact on nature. The resulting awareness influences the creative approach and practice that position themselves between the crystallizations and the metaphorical correspondences of the features of the living. This study aims to analyze the most questionable aspects of animal identity codes – especially reptiles – and their changes in order to escape the prejudice that manners and tone of the conversation may imply. REZUMAT. Scriind cu animale: ineditele opțiuni ale lui Barbey d’Aurevilly. În paginile lui Jules Barbey d’Aurevilly, prezența animalelor face posibilă reconsiderarea formelor de coabitare scripturală dintre ființele umane și cele non-umane, într-un moment în care interesul pentru știință contribuie la dezvoltarea tot mai accentuată a unei culturi ce ține seama de impactul problematic asupra naturii. Nivelul de conștientizare ce rezultă de aici influențează abordarea și practica creatoare, ce se poziționează între cristalizările și corespondențele metaforice ale datelor naturale. Studiul de față își propune să analizeze aspectele cele mai neobișnuite ale codurilor identitare animaliere – în special ale celor reptiliene - și transformările lor pentru a ocoli prejudecățile pe care le pot implica moravurile și tonul conversației. Cuvinte cheie : Barbey d’Aurevilly, animale, reptile.